2022
DOI: 10.1002/macp.202200352
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Isocyanide‐Based Step‐Growth Polymerization

Abstract: Isocyanide is an important class of active synthon with a special electronic structure and abundant chemical properties, which can participate in various organic reactions and has a wide range of applications in the efficient synthesis of pharmaceutical molecules, heterocyclic compounds, and natural products, etc. With the development of chemical science, isocyanide-based reactions have been gradually applied from the synthesis of low mass molecules to functional polymers. This review focuses on the recent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…After stone, ceramic, concrete, bronze, iron, aluminum, and steel, synthetic polymers are the most significant development for human cognition and application of matter and materials, which play important roles in anthropic production and life . The establishment of new polymerizations is an inevitable tendency in synthetic polymer chemistry and materials science, especially with the advantages of simple operation, mild conditions, high efficiency, excellent selectivity, low cost, environmental benefits, and so on. Recently, polymerizations based on triple-bond building blocks, such as Sonogashira coupling polymerization, , Glaser coupling polymerization, , polycyclotrimerization, , C–H activation polymerization, click polymerization, and multicomponent polymerization, have attracted broad attention because of their abundant reaction types and high reactivity. Moreover, the polymers generated by these powerful polymerizations contain unique unsaturated conjugated units, making them widely applicable in chemical sensor, information encryption, optoelectronic and biologic fields, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…After stone, ceramic, concrete, bronze, iron, aluminum, and steel, synthetic polymers are the most significant development for human cognition and application of matter and materials, which play important roles in anthropic production and life . The establishment of new polymerizations is an inevitable tendency in synthetic polymer chemistry and materials science, especially with the advantages of simple operation, mild conditions, high efficiency, excellent selectivity, low cost, environmental benefits, and so on. Recently, polymerizations based on triple-bond building blocks, such as Sonogashira coupling polymerization, , Glaser coupling polymerization, , polycyclotrimerization, , C–H activation polymerization, click polymerization, and multicomponent polymerization, have attracted broad attention because of their abundant reaction types and high reactivity. Moreover, the polymers generated by these powerful polymerizations contain unique unsaturated conjugated units, making them widely applicable in chemical sensor, information encryption, optoelectronic and biologic fields, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, multicomponent polymerizations (MCPs) have become a popular polymer synthesizing tool, which has gained much attention in designing new polymeric structures and regulating material properties, [12][13][14] including isocyanidebased MCPs, [15][16][17][18][19][20][21] alkyne-based MCPs, [22][23][24][25][26] elemental sulfurbased MCPs, [27][28][29] green monomer-based MCPs 30 and so forth. 31 Compared with traditional polymerizations, MCPs could provide polymers with well-defined structures, ordered sequences of monomer units, and multifunctionalities, featuring advantages of high atom economy, step effectiveness, environmental benefits, simple and inexpensive reactants, operational simplicity, and synthetic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To address the end-of-life issue of SGPs, by depolymerizing them into either their starting feedstocks or derivatives, followed by repolymerization or repurposing into virgin-quality or value-added polymersa process termed chemical recyclingpresents a promising solution. Most conventional SGPs such as polyesters, polyamides, and polycarbonates are synthesized by condensation reactionswhere difunctional or multifunctional monomers link togetherlosing small molecules as byproducts. Condensation reactions are intrinsically reversible and exist in dynamic equilibrium with their hydrolysis reactions, and an exhaustive condensation requires timely removal of byproducts from the reaction system. The presence of such byproducts detrimentally impacts the polymerization degree of resulting condensation polymers. Other types of conventional SGPs primarily including polyurethanes and polyureas are formed by addition reactions that simply link monomers without the cogeneration of byproducts . Recently, researchers found that these two addition polymers (i.e., polyurethanes and polyureas) exhibit dynamic behavior upon thermal treatment typically above 180 °C, undergoing dissociation into their constituent reactantsnamely isocyanates and hydroxyls (for polyurethanes) or amines (for polyureas), respectively. These indicate that regardless of the synthetic route (i.e., condensation and addition), most resulting SGPs inherently possess a “dynamic” characteristic; one is the equilibrium between condensation and hydrolysis reactions, and the other refers to the equilibrium between addition reactions and thermal dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of conventional SGPs primarily including polyurethanes and polyureas are formed by addition reactions that simply link monomers without the cogeneration of byproducts. 37 Recently, researchers found that these two addition polymers (i.e., polyurethanes and polyureas) exhibit dynamic behavior upon thermal treatment typically above 180 °C, undergoing dissociation into their constituent reactants� namely isocyanates and hydroxyls (for polyurethanes) or amines (for polyureas), respectively. 38−40 These indicate that regardless of the synthetic route (i.e., condensation and addition), most resulting SGPs inherently possess a "dynamic" characteristic; one is the equilibrium between condensation and hydrolysis reactions, and the other refers to the equilibrium between addition reactions and thermal dissociation.…”
Section: Introductionmentioning
confidence: 99%